The Influence of the Utilization of Artificial Intelligence (AI) on Islamic Religious Education and Character Education Learning at State Senior High School 14 Bandar Lampung - Muhammad Adib; Chairul Anwar; Bambang Sri Anggoro (al-Afkar, Journal For Islamic Studies, 2026)
The rapid development of digital technology has driven the transformation of educational practices through the integration of Artificial Intelligence (AI) as an adaptive, interactive, and data-driven learning innovation. In the context of formal education, including Islamic Religious Education (PAI), the utilization of AI has the potential to measurably enhance instructional effectiveness while simultaneously strengthening students’ cognitive and affective domains. However, its implementation must be balanced with ethical foundations and moral responsibility to minimize the risks of technological misuse. This study aims to analyze the effect of AI utilization on students’ PAI learning outcomes and character development at SMA Negeri 14 Bandar Lampung. A quantitative approach was employed using a cluster sampling technique. Data were analyzed using SPSS through the Tests of Between-Subjects Effects. The findings indicate that AI utilization has a significant effect on improving PAI learning outcomes (F = 15.528; p < 0.05), with an R² value of 0.250, suggesting that 25% of the variance in learning outcomes is explained by AI usage. Furthermore, the effect of AI on character development demonstrates a stronger influence (F = 123.594; p < 0.05) with an R² value of 0.726, indicating a substantial contribution to students’ character formation. These findings confirm that AI integration impacts not only academic achievement but also the reinforcement of values and attitudes. Future research is recommended to expand the sample scope, develop more comprehensive experimental designs, and incorporate mediating and moderating variables to gain a deeper understanding of the mechanisms through which AI influences PAI and character education learning.